SAE Technical Paper Series 2010
DOI: 10.4271/2010-01-0179
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of High-Pressure Diesel Sprays with Multiple Injections at Engine Conditions

Abstract: A numerical methodology to simulate the high pressure spray evolution and the fuel-air mixing in Diesel engines is presented. Attention is focused on the employed atomization model, a modified version of the Huh and Gosman, on the definition of a turbulence length scale limiter and of an adaptive local mesh refinement technique to minimize the result grid dependency. All the discussed models were implemented into Lib-ICE, which is a set of libraries and solvers, specifically tailored for engine simulations, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Collision and coalescence were not taken into account since they have a minimum influence when evaporating sprays have to be simulated (Baumgarten, 2006). Further details of the implementation of the primary atomization model used in this study can be found in Lucchini et al (2010) and Gong et al (2014).…”
Section: Liquid-phase Governing Equations and Spray Sub-modelsmentioning
confidence: 99%
“…Collision and coalescence were not taken into account since they have a minimum influence when evaporating sprays have to be simulated (Baumgarten, 2006). Further details of the implementation of the primary atomization model used in this study can be found in Lucchini et al (2010) and Gong et al (2014).…”
Section: Liquid-phase Governing Equations and Spray Sub-modelsmentioning
confidence: 99%
“…It was technically difficult to pressurize the air and apply a backpressure on the spray. Several studies [24][25][26] have shown that this parameter should not significantly alter the injection rate measurement, particularly at high rail pressures. No damages or erosions were noticed on the pressure sensor plate.…”
Section: Injection Rate Test Rigmentioning
confidence: 99%
“…Hence, mesh size and structure must be carefully chosen due to the well-known grid dependency problem. Following previous works, [17,18], separate models were applied to predict atomization and secondary breakup processes. This is expected to better reproduce the morphology and the evolution of sprays emerging from large nozzles.…”
Section: Spray Modelmentioning
confidence: 99%